Application of the 8th edition of the AJCC yTNM staging system shows improved prognostication in a single center cohort of esophageal carcinomas. (March 2018) - Kröll, Dino; Noser, Laura; Erdem, Suna; Storni, Federico; Arnold, Dominik; Dislich, Bastian; Zlobec, Inti; Candinas, Daniel; Seiler, Christian A.; Langer, Rupert
Abstract: Background: The 8th edition of the AJCC TNM staging system presents for the first time a specific classification for esophageal carcinomas treated with neoadjuvant therapy (yTNM8). In this single center study, we applied the novel staging system in a "real life" case series and compared the prognostic value of yTNM8 with the preceding 7th edition (TNM7). Methods: Out of 272 consecutive esophageal carcinomas that were treated during a 15-year period in one surgical center, all 198 cases that had undergone neoadjuvant therapy were reviewed and classified according to TNM7 and yTNM8. Results: 50 ypT0 cases that had no specific staging in TNM7 were included into stages I (ypT0N0M0; n = 42), IIIA (ypT0N1M0; n = 6), IVA (ypT0N3M0; n = 1) and IVB (ypT0N0M1; n = 1) in yTNM8. Both systems showed significant prognostic impact (p < 0.0001 each). yTNM8 was superior regarding prognostication with lower values for goodness-of-fit criteria (Akaike Information Criterion 1589.331 vs 1593.239; and Schwarz Bayesian Criterion 1605.487 vs.1619.088). However, in TNM7, stage IIB tumors had better prognosis than stage IIA tumors, and likewise, stage IIIA tumors better compared to stage II in yTNM8. Conclusions: yTNM8 allows accurate staging of esophageal carcinomas treated by neoadjuvant therapy, with slightly improved prognostication compared to TNM7. Additional data acquisition will be necessary for further improvement of staging for esophageal carcinomas after neoadjuvant treatment. Highlights: Single center series applying the new AJCC TNM staging system for esophageal carcinomas following neoadjuvant therapy (yTNM8). Comparison with the preceding 7th edition (TNM7). Possibility to assign a specific tumor stage for ypT0 cases. Slight superiority of yTNM8 regarding prognostication compared to TNM7. However, still no perfect prognostic discrimination in this "real life setting".